Women (cis) and illegalized drug markets. Reflections from Santa Fe (Delito y Sociedad, 2024)
This work aims to establish a dialogue between the analysis of criminalization policies and the life experiences of women detained for crimes related to the illegal drug market, by intersecting two investigations that address distinct aspects of women's imprisonment. The study reflects on the measures adopted with the emergence of drug trafficking as a public problem in the context of Santa Fe, and their effects on the incarceration of women. It explores the particularities of cis women's participation in illegal drug markets locally and examines the different interactions they have had with the penal system through the stories of those involved. Furthermore, it proposes a critical reflection on the existing literature about women's participation in illegal drug markets, challenging the predominant victimizing narrative and recognizing their agency in these contexts.
Keywords: Criminalization policies; Imprisonment of women; Illegalized drug market